Three siblings with giant axonal neuropathy caused by a novel variant in GAN gene: the first report from Egypt - Abdelrahim A. Sadek; Mohammed A. Aladawy; Tarek M. M. Mansour; Ali Farag El Hadad; Abd Elaziz Shokry; Rin Khang; Seung Woo Ryu; Elsayed Abdelkreem (Egyptian Journal of Medical Human Genetics)
Abstract Background Giant axonal neuropathy (GAN) is a rare inherited neurodegenerative disease that affects the peripheral and central nervous systems. Herein, we describe three Egyptian siblings with GAN who showed differences in clinical severity. Case Presentation. Case 1 had slowly progressive sensorimotor polyneuropathy starting from 6 years of age with lack of remarkable central nervous system (CNS) involvement till age of 14 years. In contrast, case 2 showed early-onset neurodevelopmental delay, rapidly progressive course, and significant CNS manifestations. Case 3 had an intermediate phenotype. The extent of brain imaging abnormalities paralleled the clinical severity as case 1 had only moderate white matter changes while case 2 showed extensive white matter lesions, ventriculomegaly, and atrophic changes. Whole-exome sequencing revealed a novel homozygous nonsense GAN variant c.918G > A (p.Trp306Ter). Conclusion This is the first case report of GAN from Egyptian populations, which expands the spectrum of disease-causing variants in the GAN gene and underscores the clinical heterogeneity of this disease even among patients sharing the same genotype and environmental conditions.